Religious Education Between Minorities and Majorities: Exploring the Problems of Islamic Education in Responding to the Era of Globalization and Modernity - Hermawan, Wawan; Islamy, Mohammad Rindu Fajar; Parhan, Muhamad (Jurnal Pendidikan Progresif, 2022)
Religious  Education Between Minorities and Majorities: Exploring the Problems of Islamic Education in Responding to the Era of Globalization and Modernity. Objectives: This study aims to explores the dynamics of Islamic Education discourse in Western and Eastern countries such as Indonesia in response to the Globalization Era and 21st Century Modernity   Methods: The research uses a qualitative approach, where data collection uses literature study techniques. The data we collect from scientific research with sources from Scopus, Web of Science, and Sinta. As for data analysis using Miles and Huberman steps. Findings: The different characteristics between the West, which is dominated by empirical and secular currents of thought, and Indonesia, which is based on religious values Conclusion: Islamic religious education in the West has a secular character that is based on philosophical views of rationalism, empiricism, relativism, capitalism, humanism, and positivism, in contrast to the educational process in the East, which tends to be based on religious principles based on revelations, both the Qur'an and the Qur'an. As-Sunnah. Keywords: islamic education, globalization, modernity, west, east.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202212